2008
DOI: 10.1021/jp711508b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chiral Ionic Liquids on the Excited-State Properties of Naproxen Analogs

Abstract: The synthesis and decolorization of chiral room-temperature ionic liquids based upon 1-methyl imidazole and chloromethyl menthyl ether is reported. The excellent optical quality of these solvents permits the investigation of the effects of the two enantiomers on the excited-state photophysics of (S)-Nmethyl-2-pyrrolidinemethyl 2(S)-(6-methoxy-2-naphthyl)propionate [(S,S)-NPX-PYR]. Whereas in conventional bulk polar solvents such as acetonitrile, (S,S)-NPX-PYR is known to execute excited-state intramolecular el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…A 10% difference in lifetime (∼8.9 and ∼8.1 ns) is observed in the two chiral solvents at room temperature (Figure 4), which is consistent with our previous results in the menthyl-based ionic liquids. 26 As a control, similar experiments were also done with (S)-naproxen, which is the parent compound of the dyad, and the stereodifferentiation in the lifetimes is also observed at room temperature ( Figure 5). To ensure that this discrimination is not due to impurities in the ionic liquids, (S)-and (R)-naproxen were also studied in the same ionic liquids, and a ∼10% difference in fluorescence lifetimes was observed for the two naproxen isomers ( Table 1).…”
Section: Resultsmentioning
confidence: 85%
“…A 10% difference in lifetime (∼8.9 and ∼8.1 ns) is observed in the two chiral solvents at room temperature (Figure 4), which is consistent with our previous results in the menthyl-based ionic liquids. 26 As a control, similar experiments were also done with (S)-naproxen, which is the parent compound of the dyad, and the stereodifferentiation in the lifetimes is also observed at room temperature ( Figure 5). To ensure that this discrimination is not due to impurities in the ionic liquids, (S)-and (R)-naproxen were also studied in the same ionic liquids, and a ∼10% difference in fluorescence lifetimes was observed for the two naproxen isomers ( Table 1).…”
Section: Resultsmentioning
confidence: 85%
“…119 They observed a reproducible stereodifferentiation ($ 10%) in the fluorescence lifetime of (S,S)-NPX-PYR and (S)-naproxen in 6 CIL 98 (see Fig. 24).…”
Section: Cils In Spectroscopymentioning
confidence: 89%
“…Chiral recognition, enantioselectivity, and influence of room temperature CILs (RTIL) synthesized from 1-methyl imidazole and chloromethyl menthyl ether on excited-state photophysics of (S)-N-methyl-2-pyrrolidinemethyl 2(S)-(6-methoxy-2-naphthyl)propionate [(S,S)-NPX-PYR] was recently investigated using a fluorescence lifetime [114]. The chemical structures of the CILs and chiral analytes used for the lifetime study are shown in Fig.…”
Section: Life Time Studymentioning
confidence: 99%
“…In the CILs, the lifetime is significantly increased and there is a difference in lifetime in the two solvents. Adapted from [114] Table 2 Fluorescence lifetime parameters of (S,S)-NPX-PYR and related systems. Data from [114] Ionic liquid selector and selectand system τ (ns) A similar study conducted using S-naproxen as chiral analyte also demonstrates a 10% difference in fluorescence lifetimes of S-naproxen in the presence of (+)-RTIL and (−)-RTIL [115].…”
Section: Life Time Studymentioning
confidence: 99%